LEGAL CERTAINTY OF AUTHORITY OF LOCAL REGULATIONS CONCERNING ZAKAT MANAGEMENT IN STATE ADMINISTRATIVE LAW PERSPECTIVE - Muhammad Helmi Fahrozi; Suprima Suprima (International Journal Labs, 2022)
This study wants to show a solution that the latest regulation on zakat, namely Law number 23 of 2011 concerning Zakat Management, can be the basis for the formation of regional regulations, through qualitative research methods, based on library research and emphasizing literature review. This study suggests that the formation of regional regulations on zakat management has strong legal certainty, because Indonesia is a state of law, and generally Indonesia uses state administrative law in carrying out its duties and responsibilities carried out by state administrators, in this case the government. Zakt is the main support for the life of the nation and society. Therefore, the law on zakat regulations from the legal aspect of state administration, the urgency of the formation of zakat regulations is important so that its legitimacy is regulated.